The Treatment of Gerontologie Insomnia - Siegel, Gloria S.; Lichstein, Kenneth L. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper reviews the distinctive features of a sleep in the elderly and related clinical issues. A consolidated nocturnal sleep pattern typifies middle-aged individuals in contrast to fragmented, lighter sleep in old age. Insomniac states in the elderly appear to occur at a relatively high frequency. Some of this may be due to mislabelling normal gerontologic sleep as insomnia by erroneously applying middle-aged sleep norms. Treatment for gerontologic insomnia has exclusively relied on pharmacotherapy, though this often poses additional problems. Psychological interventions might prove worthwhile, but heretofore, have not been attempted with the elderly. It was suggested that an educational approach attempting to teach age-appropriate sleep expectancies could prove fruitful with this population. It was concluded that gerontologic insomnia is a neglected area of research, particularly within the psychological domain.